Implikasi Revisi UU TNI terhadap Iklim Investasi Asing: Studi Kasus Perusahaan LG di Indonesia - Aura Nur Halizah; Sang Ayu Putu Rahayu (JOURNAL SAINS STUDENT RESEARCH, 2025)
The revision of the Indonesian National Armed Forces Law (TNI Law) has raised concerns regarding political stability and legal certainty, which significantly impact the foreign investment climate. This study examines the implications of the revision on the investment decisions of LG Energy Solution in Indonesia, which withdrew a substantial portion of its investment due to regulatory uncertainty and concerns over increased military involvement in civilian affairs. Using a normative juridical method with a statutory and case approach, the research finds that expanding military authority without clear legal boundaries can reduce investor confidence and disrupt the business environment. Therefore, the government must implement strategies such as transparent regulations, assurance of legal certainty, and effective communication with the international business community to maintain Indonesia’s competitiveness as an investment destination.